2022
DOI: 10.1097/corr.0000000000002482
|View full text |Cite
|
Sign up to set email alerts
|

There is Little or No Association Between Independently Assessed Communication Strategies and Patient Ratings of Clinician Empathy

Abstract: BackgroundQuality of care is increasingly assessed and incentivized using measures of patient-reported outcomes and experience. Little is known about the association between measurement of clinician communication strategies by trained observers and patient-rated clinician empathy (a patient-reported experience measure). An effective independent measure could help identify and promote clinician behaviors associated with good patient experience of care.Questions/purposes(1) What is the association between indepe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…The study by Brown et al [2] in this month’s Clinical Orthopaedics and Related Research ® is important because it challenges assumptions about the correlation between communication effectiveness and perceived empathy. Clinic visits between musculoskeletal providers and patients were video-recorded, patients completed post-visit questionnaires, and trained communication scholars observed the videos.…”
Section: Where Are We Now?mentioning
confidence: 99%
See 2 more Smart Citations
“…The study by Brown et al [2] in this month’s Clinical Orthopaedics and Related Research ® is important because it challenges assumptions about the correlation between communication effectiveness and perceived empathy. Clinic visits between musculoskeletal providers and patients were video-recorded, patients completed post-visit questionnaires, and trained communication scholars observed the videos.…”
Section: Where Are We Now?mentioning
confidence: 99%
“…Clinic visits between musculoskeletal providers and patients were video-recorded, patients completed post-visit questionnaires, and trained communication scholars observed the videos. The authors found little or no association of observed communication behaviors with patient-rated empathy of the clinician and concluded that either effective communication alone is insufficient for high levels of empathy or that existing measures of effective communication or empathy are inadequate or inappropriate [2]. Based on this evidence, clinicians, organizations, and systems should not spend a lot of time or money on “perfecting” communication strategies for all clinicians using our existing measures.…”
Section: Where Are We Now?mentioning
confidence: 99%
See 1 more Smart Citation
“…It’s a small wonder that one survey found that while 75% of orthopaedic surgeons believed they were communicating effectively with patients, only 21% of those patients agreed [4]. Diving deeper, it appears that even objective ratings of communication effectiveness made by trained communication scholars have little or no association with patient-rated clinician empathy [1].…”
mentioning
confidence: 99%
“…The opinions expressed are those of the writer, and do not reflect the opinion or policy of CORR ® or The Association of Bone and Joint Surgeons ® . S. S. Leopold ✉, Clinical Orthopaedics and Related Research ® , 300 S. Northwest Highway, Suite 203, Park Ridge, IL 60068, USA, Email: sleopold@clinorthop.org trained communication scholars have little or no association with patient-rated clinician empathy [1].…”
mentioning
confidence: 99%